Using new technologies to organize a secure flow of information (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The main purpose of this study is to examine the capabilities of key technologies to provide security in modern open networks. The subject of the study is the VPN and SSL/TLS protocols, the use of these technologies in the field of communications, their main features, differences and advantages, their location at the network level and their place in information security. By comparing the capabilities of these technologies, it was analyzed that although these technologies are competing technologies, they complement each other and extend existing functionality. As a result, despite the fact that the protocols have different properties, the possibility of solving various problems and processes based on their joint use was determined.
Keywords: information, information security, technology, protocol, cryptography, network, node, process